2018
DOI: 10.3389/fnins.2018.00842
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Functional Connectivity in Insular Subregions in Depressive Episodes of Bipolar Disorder and Major Depressive Disorder

Abstract: Objective: Clinically, it is very difficult to distinguish between major depressive disorder (MDD) and bipolar disorder (BD) in the period of depression. Increasing evidence shows that the insula plays an important role in depression. We aimed to compare the resting-state functional connectivity (rsFC) of insular subregions in patients with MDD and BD in depressive episodes (BDD), who had never experienced manic or hypomanic episodes when they were scanned to identify biomarkers for the identification of two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 69 publications
5
28
0
Order By: Relevance
“…This is in accordance with previous studies reporting altered functional connectivity in both the salience and interoceptive networks in humans with depression compared to healthy individuals (Manoliu et al, 2014;Harshaw, 2015). For example, Yin et al (2018) observed decreased functional connectivity of insular cortex to somatosensory and motor cortices in patients with bipolar disorder in the period of depression.…”
Section: Aberrant Resting-state Functional Connectivity Following Chrsupporting
confidence: 93%
“…This is in accordance with previous studies reporting altered functional connectivity in both the salience and interoceptive networks in humans with depression compared to healthy individuals (Manoliu et al, 2014;Harshaw, 2015). For example, Yin et al (2018) observed decreased functional connectivity of insular cortex to somatosensory and motor cortices in patients with bipolar disorder in the period of depression.…”
Section: Aberrant Resting-state Functional Connectivity Following Chrsupporting
confidence: 93%
“…Another fMRI study of BD also exhibited decreased FC from the amygdala to the TP, and this was consistent with our results [59]. Other several rs-fMRI studies have shown decreased FC of the TP in participants with psychiatric symptoms [60][61][62]. Other studies have shown TP abnormalities, including decreased gray matter density [63], reduced gray matter volume [64,65], lower mean diffusivity (re ects the microstructural integrity of white matter) [66], and decreased degree centrality (re ects the functional connections) [67] in BD patients.…”
Section: Discussionsupporting
confidence: 92%
“…The bilateral insular cortex is related to self-awareness and to the processing of emotional information, which are frequently affected in MDD 44. Previous MRI studies have reported that the insula could be a key region associated with depression 45,46. One possibility is that increased RSFC between the anterior thalamus and bilateral insula underlies emotion processing under MDD.…”
Section: Discussionmentioning
confidence: 99%